Respiration-driven proton translocation by yeast mitochondria with differing efficiencies of oxidative phosphorylation - Downie, J. A. (1973)
Measurements were made of the stoicheiometry of proton translocation coupled to respiration in mitochondria from Candida utilis where the number of functional energy-conservation sites between intramitochondrial NADH and oxygen was one in a mutant with a novel oxidase (Downie & Garland, 1972), two in sulphate-deficient cells (Haddock & Garland, 1971) or three in glycerol-limited cells (Light & Garland, 1971). The stoicheiometries of protons translocated per atom of oxygen utilized (i.e. →H(+)/2e(−) ratio; Mitchell, 1966) were close to 2.0, 4.0 and 6.0 respectively. Thus by using the same substrate (intramitochondrial NADH) and oxygen throughout, the →H(+)/2e(−) ratio is shown to be 2.0 per energy-conservation site when the number of such sites is varied from one to three.